Outside Director Stock Options and Dividend Policy - Boumosleh, Anwar (2015)
Agency theory suggests that dividends can be used to mitigate agency problems between shareholders and managers. If director stock options are granted to align the interests of directors with shareholders, we anticipate that there will be less need for external governance mechanisms such as dividends. Examining the association between outside director stock options and dividend policy, we show that outside director option compensation indeed varies inversely with dividend distribution. This result suggests that incentivizing outside directors reduces the need for external market monitoring through dividends. Controlling for the sensitivity of options to changes in dividends, we illustrate that the lack of dividend protection for stock options is not a sufficient explanation for the reduction of dividends. We also show that while investment policy might dominate the decision to offer a dividend, director stock options play an important role in determining the level of dividend paid in firms that pay dividends.